Phacoemulsification Versus Manual Small Incision Cataract Surgery in Patients With Fuchs Heterochromic Iridocyclitis. Issue 5 (September 2016) - Bhargava, Rahul; Kumar, Prachi; Sharma, Shiv Kumar; Arora, Yogesh
Abstract : Purpose: To compare the safety and efficacy of phacoemulsification and manual small incision cataract surgery (SICS) to treat cataract in patients with Fuchs heterochromic iridocyclitis (FHI). Design: A randomized, double-masked, prospective, multicenter study. Methods: Consecutive patients with cataract after FHI were randomly assigned to have phacoemulsification or manual SICS by 1 of 2 surgeons experienced in both techniques. Complications (intraoperatively and postoperatively), operative time, visual acuities, endothelial cell counts, and surgically induced astigmatism were compared. Results: At 6 months, 65 (92.8%) patients in the phacoemulsification group and 70 (92.1%) in the manual SICS group had a corrected distance visual acuity of 20/63 or better ( P = 0.974). Surgical time was significantly shorter in the SICS group (11.2 ± 2.4 minutes) than in the phacoemulsification group (14.2 ± 3.1 minutes) ( P < 0.001). The mean surgically induced astigmatism was 0.8 ± 0.2 diopters (D) in the phacoemulsification group and 1.16 ± 0.2 D in the SICS group ( P < 0.001). Endothelial cell counts at 1 week and at 6 months did not differ significantly in the phacoemulsification and SICS groups ( t test; P = 0.133 and P = 0.032, respectively). Intraoperatively, 2 (3%) eyes randomized to receive phacoemulsification and 4 (5.3%) eyes randomized to receive SICS had posterior capsular rent ( P = 0.465). Conclusions: Both techniques achieved good visual outcomes with low rates of complications. Manual SICS may be a viable alternative for cataract management in patients with FHI in settings with limited access to phacoemulsification.